Penerapan Metode Scrum Dalam Pengembangan Sistem Informasi Layanan Penjaminan Mutu Universitas Dinamika - Edo Yonatan Koentjoro; Hardman Budiardjo; Tjandrarini Tjandrarini (Universitas Multi Data Palembang, 2026)
The development of information technology has encouraged higher education institutions to adopt information systems to improve the efficiency and effectiveness of internal services, including academic quality assurance services. Universitas Dinamika, as one of the private universities in Surabaya, through the Center for Quality Monitoring and Assurance (P3M), is striving to develop a quality assurance service information system to support internal audit processes, study program performance evaluations, and quality achievement monitoring. This need is increasingly important in order to meet accreditation standards and compile self-evaluation reports. Previous research has often used the Waterfall method in information system development, but this method has limitations in addressing changing needs. The Scrum method, which is part of the Agile framework, offers a more adaptive, iterative and flexible approach. Although effective in various sectors, the application of Scrum specifically to quality assurance information systems is still rarely studied, especially in the environment of private universities in Indonesia. Therefore, this study aims to analyze and apply the Scrum method in the development of a quality assurance service information system at Universitas Dinamika so that it can present relevant, accurate, and integrated data and information across units in a sustainable manner.